A construção da interpretação: uma análise computacional de performances distintas da obra "Eterna Saudade" de Dilermando Reis - Almeida, Gustavo Henrique (2021)
This work presents a formal analysis and a computational analysis of different interpreters performing the work Eterna Saudade by Dilermando Reis. A work that has harmonic materials very characteristic of Brazilian Popular Music and strong presence of the rubato, providing several options for the performer in relation to agogic and dynamics. THE emphasis on the sound aspect, and consequently on listening, combined with harmonic analysis, formal and phraseology as a basis for understanding the work, allowed a series of studies comparisons of the recorded interpretations of two interpreters, contributing to the understanding of aspects that are not explicitly included in the score, but that occur in the interpretive process. The results from the comparative analysis of recordings through of the Sonic Visualiser software provided quantitative data about the dimensions of time and dynamics, revealing the way in which each interpreter used their knowledge of their musical specializations, as well as the interpretive strategies used to materialize and enhance their interpretation of the work. The results were satisfactory because, by pointing out similarities and dissimilarities between the recorded interpretations, they allowed understand the interpretive options addressed by each of them. The research made it possible to analysis of elements that are not always evident in the score of the work and that are important for interpretive planning, the construction of performance and for the understanding of a musical work in its entirety.